Exploring EFL students' visual literacy skills and global understanding through their analysis of Louis Vuitton's advertisement featuring Mikhail Gorbachev. Issue 1 (2nd January 2016) - Takaya, Kentei
Abstract: Visual literacy is an important skill for students to have in order to interpret embedded messages on signs and in advertisements successfully. As advertisements today tend to feature iconic people or events that shaped the modern world, it is crucial to develop students' visual literacy skills so they can comprehend the intended messages. This research explores the visual literacy skills of 23 university English as a Foreign Language (EFL) students in Taiwan majoring in English by examining how they decode messages in Louis Vuitton's advertisement featuring Mikhail Gorbachev, the last president of the Soviet Union. The participants were asked to write an essay analysing the advertisement; one group was asked to write the essay in class and the other group was asked to write the essay as a homework assignment. The findings show that none of the students in this study were able to recognize the man on the advertisement as Gorbachev when they first saw the advertisement, yet their analysis varied significantly depending on whether they worked on their essay in class or at home. While the students who wrote the essay in class merely arrived at superficial interpretations of the advertisement, most of the students who worked on the essay as a homework assignment searched for relevant information online as they worked on their essays, and this facilitated a domino effect on students' learning, in which one discovery of information led to the discovery of more information, including what Gorbachev looks like and why he is prominent, and this allowed them to arrive at deeper interpretations of the advertisement compared to the other group. The process of searching for information relevant to the advertisement also helped the students to fill gaps in their knowledge of the world and deepened their global understanding, which in turn contributed towards cultivating their overall visual literacy skills.